2012
DOI: 10.1088/1751-8113/45/37/374006
|View full text |Cite
|
Sign up to set email alerts
|

Repulsive Casimir and Casimir–Polder forces

Abstract: Abstract. Casimir and Casimir-Polder repulsion have been known for more than 50 years. The general "Lifshitz" configuration of parallel semi-infinite dielectric slabs permits repulsion if they are separated by a dielectric fluid that has a value of permittivity that is intermediate between those of the dielectric slabs. This was indirectly confirmed in the 1970s, and more directly by Capasso's group recently. It has also been known for many years that electrically and magnetically polarizable bodies can experi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 92 publications
1
28
0
Order By: Relevance
“…[65,67] Recent studies on the interactions of two materials, including NWs, separated by a thin film of fluid have shown that the Casimir[68, 69] interaction energies can be either repulsive or attractive depending on 6 the permittivities of the materials (NWs and fluids). [70][71][72] They also reported that, due to retardation effects, the separation of the two materials has a very strong influence on the permittivities,[71] which could transform the Casimir interaction energy from attractive to repulsive at intermediate separations ( 10 nm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[65,67] Recent studies on the interactions of two materials, including NWs, separated by a thin film of fluid have shown that the Casimir[68, 69] interaction energies can be either repulsive or attractive depending on 6 the permittivities of the materials (NWs and fluids). [70][71][72] They also reported that, due to retardation effects, the separation of the two materials has a very strong influence on the permittivities,[71] which could transform the Casimir interaction energy from attractive to repulsive at intermediate separations ( 10 nm).…”
Section: Discussionmentioning
confidence: 99%
“…[65] This regime is known as the relativistic retarded regime, [65] where the finite speed of light leads to significant attenuation of the dispersion interactions, [64] and the resulting fluctuations in dipole moments lead to forces known as the Casimir forces. [65,67] Recent studies on the interactions of two materials, including NWs, separated by a thin film of fluid have shown that the Casimir [68,69] interaction energies can be either repulsive or attractive depending on the permittivities of the materials (NWs and fluids). [70][71][72] They also reported that, due to retardation effects, the separation of the two materials has a very strong influence on the permittivities, [71] which could transform the Casimir interaction energy from attractive to repulsive at intermediate separations ( 10 nm).…”
Section: Discussionmentioning
confidence: 99%
“…In order to obtain a more treatable analytical solution for such a problem, we compute the non-retarded dispersion force (van der Waals force) between a quantum particle and a perfectly conducting toroid with the quantum particle lying in the symmetry axis of the toroid. Though the perfectly conducting hypothesis and short-distance regime are conflicting assumptions, this choice was made for the following reasons: (i) it will work for molecules whose dominant transition wavelengths allow the existence of a window of distances to the conducting surface that are far enough so that the surface can be considered in a first approximation as perfectly conducting but not too far away so that the retardation effects can be neglected; (ii) we expect that some important features of the interaction, like the attractive/repulsive character of the force will be essentially the same, as it occurs in the atom-plane with a hole system (this can be checked by comparing qualitatively the analytical results obtained in Ref(s) [41][42][43][44] with the exact numerical solution presented in [39]). Indeed, we show that for appropriate values of the two radii of the toroid the dispersive force on the quantum particle is repulsive.…”
Section: Introductionmentioning
confidence: 91%
“…It has been found that the Casimir force does depend on the topology as well as on the peculiar geometry of the boundaries [3,4].…”
Section: Introductionmentioning
confidence: 99%